Some General Properties of Bi-shadowing Property (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
We concentrate on bi-shadowing property, it has important properties and applications in mathematics. In this paper some general properties of this concept are proved. Let  be a metric space   be maps have bi-shadowing property. We show the maps  and  have bi-shadowing property. Let  be maps on a metric space  have  bi-shadowing property. We show the maps  and  have bi-shadowing property.